THE ROLE OF INTERNET NETWORKS IN THE DAILY LIFE OF ADOLESCENTS (European Journal of Interdisciplinary Research and Development, 2025)
This article is an attempt to show the role, positive and negative consequences of Internet networks in the daily life of adolescents.